Predictors of parasite ecology of Centrocestus formosanus (Trematoda: Heterophyidae) in Melanoides tuberculata (Caenogastropoda: Thiaridae) in a coastal wetland, Lima, Peru - Minaya, David (2024)
The aim of the present work was to determine the predictors of the parasitic ecology of Centrocestus formosanus (Trematoda: Heterophyidae) on Melanoides tuberculata (Caenogastropoda: Thiaridae) in the coastal wetland Los Pantanos de Villa (HCLPV), Lima, Peru. In total, 2532 specimens of M. tuberculata were evaluated in three lagoons: “Las Delicias”, “Mayor”, and “Marvilla”, with different levels of disturbance recorded as “high”, “medium”, and “low”, respectively, during 2009 to 2011. The largest total length (TL) of M. tuberculata occurred in Marvilla. The prevalence of C. formosanus was in sporocyst-redia (18.25%) and cercaria (24.64%). The decreasing order of prevalence for sporocyst-redia and cercaria for the lagoons was Mayor > Marvilla > Las Delicias. The sporocyst-redia presented the highest value in summer and the cercaria recorded it in the spring. Logistic regression showed that snail TL and lagoon depth were significant predictors for the prevalence of C. formosanus sporocyst-redia and cercariae. The surface water temperature of each lagoon was only a significant predictor for the sporocyst-redia. The conditional density graphs based on Bayes' theorem showed significant associations for all the variables, except for cercaria with temperature for Laguna Las Delicias, cercaria with TL for Laguna Mayor, sporocyst-redia with depth from Las Delicias lagoon, and sporocyst-redia with the LT for Lagunas Mayor and Marvilla. It is concluded that the TL of the snail, the depth and the temperature of the surface water of the lagoons were significant predictors for the parasitic ecology of the sporocyst-redia and the cercariae of C. formosanus in M. tuberculata in the HCLPV, Lima, Peru.